2019
DOI: 10.1002/gps.5167
|View full text |Cite
|
Sign up to set email alerts
|

Why deprescribing antipsychotics in older people with dementia in long‐term care is not always successful: Insights from the HALT study

Abstract: Introduction Antipsychotic medications are commonly used to manage behavioural and psychological symptoms of dementia despite their side effects and harms. While the Halting Antipsychotic Use in Long‐Term care (HALT) deprescribing trial was successful at reducing antipsychotic use, 19% of participants had their antipsychotics represcribed or never reached a dose of zero. The aim of this study was to investigate the reasons for represcription of antipsychotic medication and factors associated with ongoing antip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 37 publications
0
35
1
Order By: Relevance
“…The quality use of medicines in RACH is influenced by numerous factors that contribute to the 'prescribing culture' within the organisation [13,28] These factors include staffing levels, workload and skill mix, managerial expectations and collaboration between visiting health professionals [13,28]. These factors extend beyond the control of interventions targeted at improving clinical appropriateness of medication use for individual residents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality use of medicines in RACH is influenced by numerous factors that contribute to the 'prescribing culture' within the organisation [13,28] These factors include staffing levels, workload and skill mix, managerial expectations and collaboration between visiting health professionals [13,28]. These factors extend beyond the control of interventions targeted at improving clinical appropriateness of medication use for individual residents.…”
Section: Discussionmentioning
confidence: 99%
“…These factors extend beyond the control of interventions targeted at improving clinical appropriateness of medication use for individual residents. Interventions will likely yield greater success in improving quality use of medicines, and sustaining that improvement, if factors influencing prescribing culture and thereby the quality use of medicines within the organisation are addressed [13]. Additionally, proactive discussion between health care professionals, residents and family members is required to individualise deprescribing processes [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dementia had been suggested a long time ago to be caused by the excessive constitution of amyloid protein that leads to cell death, synaptic dysfunction, and brain atrophy [ 2 ]. However, pharmacological trials conducted to test this theory have been unsuccessful, and on the contrary, most cases worsen especially in old age [ 3 ]. Interestingly, during the recent decades, interventional epidemiology in neuroscience has been introduced where the possible interaction between the pathogenesis of dementia and various individual/environmental factors is studied, and therefore, different therapeutic protocols will be determined for various patients' subgroups [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative for residents, or their next of kin or significant other to be involved in treatment decisions. However, previous studies have reported that informed consent for antipsychotic use is infrequently documented (Aerts et al, 2019;Westaway et al, 2020). Importantly, the study by Hoyle et al focuses on assessment of outcomes important to residents and family members, such as quality of life, which is a key limitation of existing studies (Hoyle et al, 2018).…”
mentioning
confidence: 99%